ChemInform Abstract: Synthesis and Electrochemical Properties of Li4MoO5—NiO Binary System as Positive Electrode Materials for Rechargeable Lithium Batteries. Issue 15 (24th March 2016) - Yabuuchi, Naoaki; Tahara, Yoshiyuki; Komaba, Shinichi; Kitada, Satsuki; Kajiya, Yoshio
Abstract: Mixed xLi4 MoO5 /(1‐x)NiO anode materials are prepared by calcination of Lix MoS2, LiOH, and NiCO3 in air (1050 °C, 2 h).